Enhanced Oxidation Stability of Transparent Copper Films Using a Hybrid Organic‐Inorganic Nucleation Layer. Issue 5 (20th February 2019) - Bellchambers, Philip; Walker, Marc; Huband, Steven; Dirvanauskas, Aivaras; Hatton, Ross A.
Abstract: A novel seed layer for the formation of slab‐like transparent copper films on glass and plastic substrates is reported, based on a mixed molecular monolayer and an ultra‐thin (0.8 nm) aluminium layer both deposited from the vapour phase, which substantially outperforms the best nucleation layer for optically thin copper films reported to date. Using this hybrid layer, the metal percolation threshold is reduced to <4 nm nominal thickness and the long‐term stability of sub‐10 nm films towards oxidation in air is comparable to that of silver films of the same thickness fabricated using the best reported seed layer for optically thin silver films to date. The underlying reason for the remarkable effectiveness of this hybrid nucleation is elucidated using a combination of photoelectron spectroscopy, small angle X‐ray studies, atomic force microscopy and transmission electron microscopy. Abstract : A new nucleation layer for the formation of slab‐like transparent copper films on glass and plastic is reported, based on a mixed molecular monolayer and ultra‐thin (0.8 nm) aluminium layer deposited from the vapour phase. This hybrid seed layer reduces the metal percolation thickness to <4 nm and imparts dramatically enhanced long‐term stability towards oxidation in air.